2020
DOI: 10.3390/nu12051512
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a High-Protein Diet on Cardiometabolic Health, Vascular Function, and Endocannabinoids—A PREVIEW Study

Abstract: An unfavorable lipid profile and being overweight are known mediators in the development of cardiovascular disease (CVD) risk. The effect of diet, particularly high in protein, remains under discussion. Therefore, this study examines the effects of a high-protein (HP) diet on cardiometabolic health and vascular function (i.e., endothelial function, arterial stiffness, and retinal microvascular structure), and the possible association with plasma endocannabinoids and endocannabinoid-related compounds in overwei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Tischmann et al [33] revealed that a high-protein diet lasting for approximately 34 months had no signi cant effect on the biomarkers of cardiometabolic health and vascular function in overweight participants. In contrast, a previous study [34] reported that high-protein diets can decrease the levels of low-density lipoprotein, total cholesterol, and triglycerides as well as mitigate insulin resistance in patients with type 2 diabetes mellitus. The differences with our study may be associated with the metabolic disorder in diabetic patients and shorter duration of our study.…”
Section: Discussionmentioning
confidence: 60%
“…Tischmann et al [33] revealed that a high-protein diet lasting for approximately 34 months had no signi cant effect on the biomarkers of cardiometabolic health and vascular function in overweight participants. In contrast, a previous study [34] reported that high-protein diets can decrease the levels of low-density lipoprotein, total cholesterol, and triglycerides as well as mitigate insulin resistance in patients with type 2 diabetes mellitus. The differences with our study may be associated with the metabolic disorder in diabetic patients and shorter duration of our study.…”
Section: Discussionmentioning
confidence: 60%
“…A study that assessed overweight adults revealed that AEA, 2-AG, OEA, and PEA were all positively associated with body fat percentage and that OEA was positively associated with heart rate, total cholesterol, and LDL cholesterol, whereas PEA was positively associated with total cholesterol, LDL cholesterol, and HDL cholesterol [ 35 ]. Our findings are consistent with some of those results, as we found a positive correlation of PEA and OEA with HDL cholesterol but a negative correlation with LDL cholesterol, leading to a negative correlation with the LDL/HDL ratio.…”
Section: Discussionmentioning
confidence: 99%
“…An unhealthy diet constitutes a major modifiable behavioral risk factor because it exerts a deleterious impact, via long-term effects, on the majority of classic risk factors and metabolic parameters. The interplay between various dietary patterns and CVD has long been investigated under the scope of discovering potential links with hypertension (HTN), dyslipidemia, impaired glucose metabolism and insulin resistance, obesity, and even chronic inflammation and oxidative stress [ 3 , 4 , 5 , 6 , 7 ]. Of note, Ge et al, in a meta-analysis including 21,942 participants, compared the efficacy of 14 popularly named dietary programs, in terms of weight loss and cardiovascular risk reduction, and found that low carbohydrate–high protein (HP) diets, such as the Atkins; low-fat diets, such as the Ornish; moderate macronutrient ones, such as the DASH and Mediterranean, exhibited a significant reduction in weight and blood pressure after 6 months compared to average diets.…”
Section: Introductionmentioning
confidence: 99%
“…Cut-off values for HP diets in the literature are highly heterogenous and often arbitrary. Based on energy intake, they vary from 15% up to 30% including both clinical studies and meta-analyses [ 7 , 10 , 29 , 42 , 43 ]. Based on grams of protein per kg of body weight (BW), high protein diets seem to range from 1.2 to 1.6 g/kg/day [ 9 ].…”
Section: Introductionmentioning
confidence: 99%